Penerapan Teknologi IoT Pada Tanaman Hidroponik Untuk Monitoring Pertumbuhan Tanaman di Desa Puccadi - Heri, Adi; Insani, Chairi Nur; Irianti, Arnita; Rasyid, Nurdina (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Technological development is needed for a better development system. Technology can provide basic changes for society, especially in the context of improving the quality of life in society. In general, the hydroponic method is carried out using water as a medium, where the water conditions that need to be considered are the supply of water, oxygen, nutrients, pH, and light intensity. UV light replaces sunlight which can help plants need the photosynthesis process which produces food substances such as carbohydrates so that plants grow faster. From the situation analysis, it is known that most of the people in Puccadi Village. Cultivating plants using a hydroponic system on a household scale by utilizing yards or yards has quite a large potential. Based on this background, IoT-based hydroponic training and assistance were carried out for the people of Puccadi Village, Luyo District. This service activity is implemented in the form of training and mentoring with the aim of participants being able to directly practice applying IoT to hydroponic plants for monitoring plants. The conclusion of the IoT-based hydroponic training activities in Puccadi Village, Luyo District, is that the implementation of IoT-based hydroponic training and mentoring went well and was able to provide knowledge related to the application of IoT technology to the Puccadi village community, Luyo District.